Respuesta :

Answer:

3

Step-by-step explanation:

1st step:  (6-5) = 1; you now have:

[4 - 5 - 7(1) + 7)] + 4

2nd step:  7(1) = 7; you now have:

[4 - (5 - 7 + 7)] + 4

3rd step:  5 - 7 + 7 = 5; you now have:

[4 - 5] + 4, which is (-1 + 4) which equals 3

[tex]\huge\text{Hey there!}[/tex]

[tex]\huge\textsf{[4 - (5 - 7(6 - 5) + 7)] + 4}[/tex]

[tex]\huge\textsf{6 - 5 = \bf 1}[/tex]

[tex]\huge\textsf{4 - (5 - (7)(1) + 7) + 4}[/tex]

[tex]\huge\textsf{7(1) = \bf 7}[/tex]

[tex]\huge\textsf{4 - (5 - 7 + 7) + 4}[/tex]

[tex]\huge\textsf{5 - 7 = \bf -2}[/tex]

[tex]\huge\textsf{4 - (-2 + 7) + 4}[/tex]

[tex]\huge\textsf{4 - 5 + 4}[/tex]

[tex]\huge\textsf{4 - 5 = \bf -1}[/tex]

[tex]\huge\textsf{-1 + 4}[/tex]

[tex]\huge\textsf{= \bf 3}[/tex]

[tex]\boxed{\boxed{\huge\textsf{{Therefore, your ANSWER is: 3}}}}\huge\checkmark[/tex]

[tex]\huge\textsf{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\huge\boxed{\frak{Amphitrite1040:)}}[/tex]